Case Study of Implementation of Slow Deep Breathing Therapy to Reduce Pain in Gastritis Sufferers - Alfirdaus, Alisa Fikri Aulia Nurul Hidayah; Permatasari, Wulan; Hamdani, Dadi; Hidayat, Nur (KIAN JOURNAL, 2023)
Objective: To present nursing care with slow deep braething intervention in an effort to reduce the intensity of heartburn in gastritis clients. Methods: The subject of this case study was a client who experienced pain associated with an injury to a biological agent. Data collection techniques are interviews, observation, physical examination, and paper research. Results: The results of the case study at the assessment stage showed that the client experienced heartburn, felt nauseous, and dizzy. The client looks in pain with a smirk on his face in pain. The established diagnosis is acute pain associated with an injury biological agent which refers to the SDKI book. The intervention and implementation used on clients is the application of non-pharmacological slow deep breathing therapy. Conclusion: After implementing slow deep breathing therapy the client says the pain has decreased slightly, while the subjective data from the history of the client looks fresh and can move as usual.